2021
DOI: 10.1002/prp2.860
|View full text |Cite
|
Sign up to set email alerts
|

Stability investigations of cytochrome P450 (CYP) enzymes immediately after death in a pig model support the applicability of postmortem hepatic CYP quantification

Abstract: Quantification of drug‐metabolizing cytochrome P450 (CYP) isoforms using LC–MS/MS has been proposed as a potential way of estimating antemortem CYP levels using postmortem tissue, but the postmortem stability of CYP proteins is incompletely investigated. If one can use data obtained from the analysis of postmortem specimens to inform physiologically based pharmacokinetic (PBPK) models this greatly increases the access to rare specimens among special subpopulations. In this study, we developed and validated an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Both studies found PMI and temperature to be very important for the protein stability of the CYP isoforms, and low MPPGL has been associated with postmortem degradation (Hansen et al, 2019;Pedersen et al, 2021). In the study by Pedersen et al 2021, both MPPGL and the concentration of CYP isoforms (pmol/mg microsomal protein) decreased as the liver was putrefied. In the current investigated population, there was a clear positive correlation between MPPGL (using a rising MPPGL cut-off level) and CYP levels (Figure 2), which is in contrast to results by Zhang et al 2015(Zhang et al, 2015 who found no association between MPPGL content and CYP activities.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Both studies found PMI and temperature to be very important for the protein stability of the CYP isoforms, and low MPPGL has been associated with postmortem degradation (Hansen et al, 2019;Pedersen et al, 2021). In the study by Pedersen et al 2021, both MPPGL and the concentration of CYP isoforms (pmol/mg microsomal protein) decreased as the liver was putrefied. In the current investigated population, there was a clear positive correlation between MPPGL (using a rising MPPGL cut-off level) and CYP levels (Figure 2), which is in contrast to results by Zhang et al 2015(Zhang et al, 2015 who found no association between MPPGL content and CYP activities.…”
Section: Discussionmentioning
confidence: 94%
“…Another major limitation of this study is the likely presence of postmortem degradation in our dataset. The postmortem stability of CYP1A2 and CYP3A4 was previously investigated in a postmortem population (Hansen et al, 2019), and using a porcine animal model (Pedersen et al, 2021). Both studies found PMI and temperature to be very important for the protein stability of the CYP isoforms, and low MPPGL has been associated with postmortem degradation (Hansen et al, 2019;Pedersen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations